2016
DOI: 10.1021/acs.macromol.6b00666
|View full text |Cite
|
Sign up to set email alerts
|

A Reptation Model of Slip at Entangled Polymer–Polymer Interfaces

Abstract: Interfaces between immiscible polymer melts can exhibit significant slip when subjected to large shear stresses. We describe and analyze a slip-link/tube model of the nonlinear steady-state rheology of an interface between entangled immiscible polymer melts. The model assumes that near equilibrium shear stress is transmitted across such an interface primarily by chains that form loops across the interface and entangle with chains of the other species. Such binary interfacial entanglements can be created by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…(19). Equation (17) can be used to obtain an effective equation of motion for the deformation tracer immobilized in the elastic component. The spatial position U(t) of such a tracer with respect to an arbitrary reference point (that can be conveniently chosen as the origin of coordinates r = 0) is given by U α (t) = (2π)…”
Section: P-2 Localization and Diffusion Of Tracer Particles In Viscoementioning
confidence: 99%
See 1 more Smart Citation
“…(19). Equation (17) can be used to obtain an effective equation of motion for the deformation tracer immobilized in the elastic component. The spatial position U(t) of such a tracer with respect to an arbitrary reference point (that can be conveniently chosen as the origin of coordinates r = 0) is given by U α (t) = (2π)…”
Section: P-2 Localization and Diffusion Of Tracer Particles In Viscoementioning
confidence: 99%
“…[17,18]). The present analysis is however done entirely within the original description [10] in order to demonstrate what should be expected in its framework.…”
Section: P-2 Localization and Diffusion Of Tracer Particles In Viscoementioning
confidence: 99%
“…Under a fast and large deformation flow field common in material processing, rheology and chain dynamics of immiscible blends are rather complex because they not only depend on the interplay between thermodynamics and kinetics in the phase separation process but also strongly correlate with the interface, especially the intricate topological constraints at the interface (i.e., interfacial entanglements). For example, upon start-up of fast shear flow, in contrast to the one-component polymer melts or the miscible polymer blends, the immiscible polymer blends usually show velocity slip at polymer–polymer interfaces, which is often seen as a signature for interface yielding and qualitatively attributed to the lower viscosity in the interfacial region than in the bulk. , When the steady state is reached, with the interfacial polymer chains oriented, deformed, and disentangled, it is assumed that the dominant mechanism of interfacial friction changes from entangled loops to unentangled loops and the slip velocity ( V s ) increases. , Meanwhile, since the interfacial shear stress σ numerically reflects the overall contribution of interfacial entanglements and unentangled loops to the momentum transfer across the interface, the interfacial stress is expected to follow a power-law behavior with the interfacial slip velocity and its exponent macroscopically represents whether the interface under shear flow is entangled or not. Furthermore, for entangled polymer melts, the reduction in interchain constraints of polymers at high shear rates may lead to the onset of retraction or tumbling cycles of the individual molecules, and particularly with the entanglement network disintegration, as the chains strongly disentangle, the chain molecule begins to tumble in a hairpin-like configuration as observed via nonequilibrium molecular dynamics simulations of monodisperse entangled polymer melts. So far, experiments , , and theoretical studies , have focused on the slip behaviors of the entangled polymer–polymer interface in binary blends and suggested that there exists a strong nonlinear dependence of the slip velocity on interfacial stress, but the quantitative details are quite different. For example, the theory of Brochard-Wyart and de Gennes predicts a stick–slip transition with the power law from V s ∝ σ ∞ to σ 1 , corresponding to a microscopic transition from a (weakly) entangled interface with a low slip velocity to an unentangled interface with a quite high slip velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental research of this kind is essential for the functionalization and design of some polymer processing additives that are added into molten polymer blends to suppress slip. 4,5,8 Moreover, such knowledge can become important for understanding the physical aspects that underlie complex rheological behaviors of polymer systems and controlling the material properties in response to any external flow field. It is worth emphasizing that the fixation of joint points of copolymers at the interface between binary immiscible homopolymers opens up the opportunity for a convenient and intuitive exploring of the interactions, motions, conformational changes, and entanglement structures of interfacial molecules while it is rather hard or even inaccessible to track the movement of any one interfacial chain in binary blends over a long period of time because of the short interfacial residence time.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are known to slip over the surface on which they flow under essentially all circumstances. In the case of polymer melts, within the first few layers, the chains adsorb on the surface, resulting in the formation of tails, loops, and trains, ,, which are in turn entangled to various degrees and at multiple sites with the bulk. When subjected to flow, adhesive slip occurs when the polymer chains detach/desorb themselves completely from the wall.…”
Section: Introductionmentioning
confidence: 99%